Inklusi Keuangan dan Pengaruhnya terhadap Penggunaan Financial Technology Pada Generasi Milenial - Rizki Sri Lasmini; Yolandafitri Zulvia (Universitas Negeri Padang, 2021)
Financial inclusion is an increase in a person's understanding and ability to determine the required financial products or services that will increase the using of them. This study to investigated the relationship between financial inclusion to financial technology utilization of student in Universitas Negeri Padang. This study is quantitative by using questionnaire to get the primary data. The questionnaire was distributed to 300 students who understand financial management. After testing the hypothesis in this study using the Structural Equation Model (SEM), the results show that financial inclusion has a positive and significant relationship to financial technology.